2016
DOI: 10.1158/0008-5472.can-15-1545
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Signaling Intersects with CD103 Integrin Signaling to Promote T-Lymphocyte Accumulation and Antitumor Activity in the Lung Tumor Microenvironment

Abstract: Homing of CD8þ T lymphocytes to the tumor microenvironment is an important step for mounting a robust antitumor immune response. TGFb is responsible for CD103 (a E b 7 ) integrin induction in activated intraepithelial CD8 þ T lymphocytes. However, the interplay between TGFb and CD103 and their contribution to T-cell infiltration and antitumor activity remain unknown. Here, we used viable human lung tumor slices and autologous tumor antigen-specific T-lymphocyte clones to provide evidence that CD103 is directly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 46 publications
3
92
0
Order By: Relevance
“…The TGF-β receptor was upregulated (FC = 2.75) in brain CD103 + CD8 T cells, consistent with previous reports of the requirement for TGF-β in generation of this population (46, 47). Notably, the pro-inflammatory cytokine Tnf is significantly upregulated in CD103 + CD8 T cells (FC = 2.5 relative to brain CD103 − ) (Figures 4B–D; Figure S5 in Supplementary Material).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The TGF-β receptor was upregulated (FC = 2.75) in brain CD103 + CD8 T cells, consistent with previous reports of the requirement for TGF-β in generation of this population (46, 47). Notably, the pro-inflammatory cytokine Tnf is significantly upregulated in CD103 + CD8 T cells (FC = 2.5 relative to brain CD103 − ) (Figures 4B–D; Figure S5 in Supplementary Material).…”
Section: Resultssupporting
confidence: 91%
“…Expression of CD103 can define a resident memory T cell, yet the T RM phenotype is not restricted to CD103 expression, nor is CD103 expression exclusive to this subset (13, 47, 49–51). This is seen in our data with flow cytometry and immunohistochemistry data revealing expression of CD103 by CD4 + T cells and dendritic cells in the Toxoplasma -infected brain and CD8 + T cells (Figure 2; Figure S7 in Supplementary Material and data not shown) (52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, studies performed with viable human tumor slices [30] and autologous tumor antigen-specific CTL clones showed that CD103 contributes to T-cell recruitment within epithelial tumor regions and enhances intratumoral T-cell early signaling [31]. Indeed, recruitment of CD8 + T lymphocytes within epithelial tumor islets was inhibited by anti-CD103 neutralizing monoclonal antibodies (mAb), while TGF-β enhanced CD103-dependent T-cell movement toward epithelial tumor regions [31]. In this context, studies from one of our groups showed that CD103 mediates arrest of T lymphocytes under flow by interacting with E-cadherin on epithelial tumors [32].…”
Section: Introductionmentioning
confidence: 75%
“…The intra-epithelial location of CD103 + CD8 + T cells was also observed in colorectal and bladder cancers, and was associated with expression of E-cadherin on tumor cells [28, 29]. Consistently, studies performed with viable human tumor slices [30] and autologous tumor antigen-specific CTL clones showed that CD103 contributes to T-cell recruitment within epithelial tumor regions and enhances intratumoral T-cell early signaling [31]. Indeed, recruitment of CD8 + T lymphocytes within epithelial tumor islets was inhibited by anti-CD103 neutralizing monoclonal antibodies (mAb), while TGF-β enhanced CD103-dependent T-cell movement toward epithelial tumor regions [31].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation